Agricultural Export Assistance to Small and Medium Enterprises in North Central Highlands – Situation and Suggestions - Chi, Nguyen Thi Minh; Sa, Dao Thi Ly (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2018)
Recently, the export turnover in the North Central Highlands has not reached the expected results. This means that export activities will face many difficulties and challenges. The main reasons are the unfavorable situation of coffee export, rubber prices remain low. Meanwhile, most of small and medium enterprises (SMEs) are not capable of exporting directly, mainly through export, so the export value is not calculated for the province. Strategic development, trade promotion, forecasting and analysis of market volatility have not been effective. This paper aims to analyze the current situation of agricultural export assistance for SMEs in the region. As results, that will be the basis to improve the quality of assistance aiming to promote growth of the agricultural sector as well as revenue for the region. Keywords North Central Highlands; small and medium enterprise; assistance; agricultural product; export References Đỗ, T. H. (2016). Chính sách hỗ trợ ngành chế biến xuất khẩu gỗ phát triển. Tạp chí tài chính, Kỳ II tháng 10/2016. Francis, J., & Collins-Dodd, C. (2004). Impact of export promotion programs on firm competencies, strategies and performance: The case of Canadian high-technology SMEs. International Marketing Review, 21(4/5), 474-495. Jaud, M., & Kukenova, M. (2011). Financial development and survival of African agri-food exports. Nguyễn, T. M. (2003). Những giải pháp phát triển dịch vụ hỗ trợ xuất khẩu chủ yếu đối với doanh nghiệp vừa và nhỏ ở Việt Nam Đề tài khoa học cấp bộ. Hà Nội: Viện Nghiên cứu thương mại. Shamsuddoha, A., Ali, M. Y., & Ndubisi, N. O. (2009). Impact of government export assistance on internationalization of SMEs from developing nations. Journal of Enterprise Information Management, 22(4), 408-422. Sousa, C. M., & Bradley, F. (2009). Effects of export assistance and distributor support on the performance of SMEs the case of Portuguese export ventures. International Small Business Journal, 27(6), 681-701. Tesfom, G., & Lutz, C. (2008). Evaluating the effectiveness of export support services in developing countries: a customer (user) perspective. International Journal of Emerging Markets, 3(4), 364-377. Trần, B. T. (2007). Đa dạng hoá dịch vụ tài chính cho xuất khẩu của doanh nghiệp vừa và nhỏ Việt nam.